2000
DOI: 10.1063/1.1308545
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio investigations of Li−+nH2→LiH2−(H2)n−1,n=1–3

Abstract: Correlated ab initio investigations on the intermolecular and intramolecular potential energy surfaces in the ground electronic state of the O 2 − ( X Π g 2 ) − HF ( X Σ + 1 ) complex J. Chem. Phys. 138, 014304 (2013); 10.1063/1.4772653Ab initio analytical potential energy surface and quasiclassical trajectory study of the O + ( 4 S)+ H 2 (X 1 Σ g + )→ OH + (X 3 Σ − )+ H ( 2 S) reaction and isotopic variants Ab initio investigations at the coupled-cluster single double ͑triple͒ ͓CCSD͑T͔͒ and MRCISD level with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…The theoretical interest in the LiH Ϫ has increased since the electron affinity ͑EA͒ of LiH and its deuterated counterpart LiD were measured with the use of the photoelectron spectroscopy by Bowen and co-workers. 4 The adiabatic electron affinities of 7 LiH and 7 LiD determined in that experiment were 0.342Ϯ0.012 eV for the former and 0.337Ϯ0.012 eV for the latter system. The appearance of these data posed a challenge for theory to reproduce those values in rigorous calculations based on the first principles.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…The theoretical interest in the LiH Ϫ has increased since the electron affinity ͑EA͒ of LiH and its deuterated counterpart LiD were measured with the use of the photoelectron spectroscopy by Bowen and co-workers. 4 The adiabatic electron affinities of 7 LiH and 7 LiD determined in that experiment were 0.342Ϯ0.012 eV for the former and 0.337Ϯ0.012 eV for the latter system. The appearance of these data posed a challenge for theory to reproduce those values in rigorous calculations based on the first principles.…”
Section: Introductionmentioning
confidence: 84%
“…In essence, one should be able to describe this situation well with such methods as the coupled cluster ͑CO͒ approach ͓with single ͑S͒, double ͑D͒, and triple ͑T͒ excitations͔ or with MRCI method provided that a sufficiently complete basis set is used. However, despite the use of the most advanced techniques and extended basis sets the calculated values ͑CCSDT of 0.327 eV 7,8 and MRCI of 0.319 eV 7 ͒ have come short of the experimental result.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…SORCI can be considered as an individually selecting approximation to the iterative DDCI3 method,40 which includes active-space configurations only with two holes and one particle or two particles and one hole, in addition to DDCI2 excitations. The most straightforward MRCI method applied here includes all single and double excitations (MRCISD) 44,45. The effects of excitations higher than doubles were included in all the MRCI excitation energies with the MR-Davidson +Q corrections 43.…”
Section: Computational Detailsmentioning
confidence: 99%
“…3 In contrast, the isomeric geometric configuration of the weakly bound electrostatic complex, Li Ϫ (H 2 ), has attracted much less attention. Recently, this complex was studied theoretically 4 in the context of the insertion reactions, Li Ϫ ϩnH 2 →HLiH Ϫ (H 2 ) nϪ1 , with special emphasis placed on the mechanistic changes induced by the number of H 2 molecules present. Exploration of the nϭ1 potential energy surface ͑PES͒ in that study 4 identified some regions where the anionic and neutral PESs cross all of which were far from the electrostatic complex geometry.…”
Section: Introductionmentioning
confidence: 99%